Prevalence of breast masses and barriers to care: Results from a population‐based survey in Rwanda and Sierra Leone. Issue 8 (2nd August 2014) - Ntirenganya, Faustin; Petroze, Robin T.; Kamara, Thaim B.; Groen, Reinou S.; Kushner, Adam L.; Kyamanywa, Patrick; Calland, J. Forrest; Kingham, T. Peter
ABSTRACT Background and Objectives Breast cancer incidence may be increasing in low‐ and middle‐income countries (LMIC). This study estimates the prevalence of breast masses in Rwanda (RW) and Sierra Leone (SL) and identifies barriers to care for women with breast masses. only. Methods Data were collected from households in RW and SL using Surgeons Overseas Assessment of Surgical Need (SOSAS), a cross‐sectional, randomized, cluster‐based population survey designed to identify surgical conditions. Data regarding breast masses and barriers to care in women with breast masses were analyzed. Results 3, 469 households (1, 626 RW; 1, 843 SL) were surveyed and 6, 820 persons (3, 175 RW; 3, 645 SL) interviewed. Breast mass prevalence was 3.3% (SL) and 4.6% (RW). Overall, 93.8% of masses were in women, with 49.1% (SL) and 86.1% (RW) in women >30 years. 73.7% (SL) and 92.4% (RW) of women reported no disability; this was their primary reason for not seeking medical attention. Overall, 36.8% of women who reported masses consulted traditional healers only. Conclusions For women in RW and SL, minimal education, poverty, and reliance on traditional healers are barriers to medical care for breast masses. Public health programs to increase awareness and decrease barriers are necessary to lower breast cancer mortality rates in low‐ and middle‐income countries (LMIC). J. Surg. Oncol. 2014; 110:903–906. © 2014 Wiley Periodicals, Inc.